Project management: a new service delivery paradigm - G. van der Walt (Koers : Bulletin for Christian Scholarship, 2007)
In line with international trends in governance, the South African Government’s initial focus on the development of policy frameworks, structures and systems in order to give effect to the values and principles of the Constitution, shifted to the most critical issue, namely service delivery. The Government became increasingly aware that a significant expansion in the scope and quality of service provision was not possible with traditional delivery settings and approaches. There is growing evidence that there is a need for a significant departure from conventional approaches and that a leap into a new service delivery paradigm is necessary. Increasingly this new paradigm highlights the need to further develop the government’s project management skills and applications with a view to achieving improved delivery capability.